English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Let f(x) = 2e^4x - 1 and g(x) = 4e^4x + 3.
lim.........f(x) .
x=>oo.....g(x)

2006-10-14 04:41:05 · 1 answers · asked by chris 2 in Science & Mathematics Mathematics

1 answers

Do you mean lim (x->inf) f(x) / g(x) ?

Let u=e^x. Then, since u->inf as x->inf, you can rewrite this as

lim(u->inf) (2u^4 - 1) / (4u^4 + 3).

Divide the numerator and denominator by u^4. You get

lim(u->inf) (2 - 1/u^4) / (4 + 3/u^4).

As u->inf, 1/u^4 -> 0, so you're left with 2/4 = 1/2.

2006-10-14 04:44:49 · answer #1 · answered by James L 5 · 0 0

fedest.com, questions and answers